The impact of ethanol driven corn price on the cow-calf industry - Warner, Marcella M. (Kansas State University, 2008)
After remaining stable for several decades, corn price has recently had unprecedented price increases and volatility. United States Department of Agriculture (USDA) predicts an average corn price of $5.80 per bushel for 2008, which is 232% of its 28-year (1980-2007) average price of $2.50. The record increase in corn price was the result of increased starch-based ethanol production associated with increased energy costs, and other factors such as a declining value in the United States dollar, and increased global commodity demand. High corn prices have impacted the profitability of the livestock feeding industry. It was less clear how the record high corn prices would affect the cow-calf industry since corn is not a significant input for cow-calf enterprises. This study quantified the relationship between cow-calf profitability and corn price. Because feed costs for a cow-calf producer are among the highest variable costs for the operation, both grazing and non-grazing feed costs were estimated as a function of corn price. Models were estimated to determine if a relationship between corn price and Returns Over Variable Costs (ROVC) at the cow-calf level could be identified. Corn price from 1978-2007 explained none of the variability in grass grazing rental rate, however when the projected 2008 corn price was included in the analysis, corn price explained 10% of the variation in grass grazing rates. Year (linear time trend) and corn price from 1978-2008 explained 88% of historical grass grazing rental rate variability, 71% of alfalfa price variability, and 63% of other hay price variability in Kansas. These results suggest that the new corn market paradigm likely will increase the relationship between corn price and feed costs at the cow-calf level. Several models were evaluated using bulk diesel fuel price, feeder calf price, corn price, alfalfa price, other hay price, and grass grazing rental rate to estimate Kansas cow-calf producer ROVC. Models that included diesel fuel price, feeder calf price, grazing rent, and one of the harvested feeds (corn, alfalfa, or other hay) price explained 90-91% of the variability in ROVC. Models that included diesel fuel price, feeder calf price, and either grazing rent or corn price explained less of the variability in ROVC; using grazing rent explained 89% and using corn price explained 79%. Including grass grazing rental rate along with corn price, feeder calf price, and bulk diesel fuel price improved the model's ability to predict ROVC, explaining 91% of the variability. While cow-calf producers might use very little corn directly in their operations, this research shows that corn price is an important determinant of cow-calf production returns, and corn price can be used by producers to plan for future rising costs in order to maximize returns.
Keywords: Cow-Calf; Returns; Costs; Feed; Inputs; Energy; Agriculture, Animal Culture and Nutrition (0475); Agriculture, General (0473); Economics, Agricultural (0503)